Development and application of a numerical analysis method for investigating hydro static and hydrodynamic responses of pocket bearing rotor systems. (February 2022) - Chellapandi, P.; Rao, C. Lakhmana
Abstract: A numerical tool is presented for simulating the dynamics of a vertical rotor attached with pocket bearing assembly immersed in a liquid pool. The journal of the bearing has a heterogeneous geometry with the presence of pockets and grooves. The fluid pressure supplied to the pockets is a quadratic function of shaft speed. The radial, circumferential and axial flow paths constitute a complex fluid network in the coupled system. The network has been conceived as an assemblage of straight and curved fluid flow paths for the generic applications. An efficient solution strategy has been employed involving both analytical and numerical techniques. A Case study was performed on a representative pocket bearing assembly that is commonly used in the coolant pumps of sodium cooled fast reactor. The study has brought out some specific dynamic characteristics of such bearings. The flow field exhibits both hydrostatic and hydrodynamic effects, thereby hybrid bearing characteristics. The dynamic characteristics are strong function of spinning velocity, eccentricity and angular orientation of the rotor in fluid annulus. Based on an elaborate parametric study, a rotor dynamic stability chart has been established for the practical applications. Interestingly, the dynamic behavior within a limited operating regime exhibits the characteristics of a large eccentric homogeneous rotor rotating in fluid annulus with moderate gaps, predicted by Antunes et al. (1996). Moreover, it is found that the pocket type bearing has better stability control, mainly due to lower added fluid mass. The numerical tool is experimentally validated by comparing the displacements measured on a shaft coupled with pocket bearing assembly, rotating in a water pool. Highlights: A numerical tool for predicting the dynamics of rotor coupled with heterogeneous pocket bearing assembly, immersed in a liquid pool is presented. An efficient solution strategy is adopted with both analytical and numerical techniques for performing barring design optimization studies. Through a case study, hydro static and dynamic characteristics are brought out for hybrid bearings immersed in fluid annulus with moderate gaps. The pocket type hydrostatic bearings have superior stability characteristics over the practical operating regimes. The numerical tool is experimentally validated to ensure its applicability for the practical shaft-pocket baring coupled systems.